Research and design for fashion - Seivewright, Simon; Sorger, Richard (Basics fashion design., 2017)
"The ability to generate inspired ideas is vital in all creative industries, and nowhere is this more true than in the fast-paced and trend-driven fashion industry. A bestseller in both the UK and US, this fully revised third edition of Research and Design uniquely provides a handy and indispensable resource that will gently guide readers through the fashion design process.Comprising a complete toolkit of key need-to-know topics, Research and Design demonstrates how important fashion design research is to the creation of inspired designs and concepts. Topics explored include choosing themes, compiling research, using your sketchbook as a design tool, techniques for drawing, and collage, juxtaposition and deconstruction, as well as how to design from your research, design development, working with the colour wheel, and how to successfully communicate your ideas, fully equipping readers with all the knowledge and tools needed to embark on their own design projects. Now fully revised and updated with beautiful and inspiring new visuals from the studio, designers' portfolios, and the catwalk, as well as exciting new case studies, interviews with practising fashion designers, and practical exercises, Research and Design will show readers how to excel in carrying out professional fashion research and design."--